Myocardial Infiltration in Primary Mediastinal B-Cell Lymphoma Detected by Cardiac Magnetic Resonance Imaging - Sutedjo, Verawati; Soewondo, Widiastuti; Yuniarti, Mira; Tenggara, Jeffry Beta; Erawati, Dini Rachma (http://dharmais.co.id/, 2023)
Introduction: Cardiac involvement, particularly myocardial infiltration in primary mediastinal lymphoma, is a rare occurrence with an incidence of only 9% in known cases of primary malignancy. Neoplasm infiltration into the myocardium manifests through direct invasion, hematogenous spread, transvenous invasion through the great veins, or lymphangitic spreading in the mediastinal. Myocardial infiltration in lymphoma presents a grim prognosis and its treatment may be associated with specific risks, such as myocardial rupture. Various imaging modalities may detect cardiac involvement, with cardiac magnetic resonance (CMR) imaging considered the gold standard. CMR enables clear delineation of myocardial infiltration, making it valuable for local staging, pretreatment planning, and evaluating treatment response. Case Presentation: : A 37-year-old woman patient was diagnosed with primary mediastinal large B-cell lymphoma. Mild chest discomfort and shortness of breath were observed 3 months before hospital admission. A thorax CT scan showed a heterogeneous contrast-enhancing mass with a central necrotic area in the anterior mediastinum. Following thoracotomy and tumor debulking, the patient complained of severe crushing chest pain radiating to her back, accompanied by new T wave inversion on ECG and elevated cardiac troponin levels a week after surgery. Coronary angiogram results showed a normal coronary artery. Subsequent cardiac MRI showed tumor infiltration into the anterior pericardial space, as well as the myocardium of the left and right ventricles. Chemotherapy was promptly initiated, resulting in a gradual improvement of symptoms. Conclusions: In this study, we discuss the use of 3D-CRT in the re-irradiation of NPC with its limitation on obtaining optimum dose sculpture compared to more sophisticated and widely spread modalities like IMRT. However, with careful planning, we can still obtain optimum tumor dose, minimize OAR dose, and subsequently late toxicities that come after. We hope that this study can bring hope to centers with limited facilities, and we suggest further studies on reirradiation, especially in OAR dose tolerance guidelines.